EXPERIMENTAL MEASUREMENTS AND THERMODYNAMIC MODELING OF CARBON DIOXIDE SOLUBILITY IN BLENDS OF AQUEOUS POTASSIUM LYSINATE WITH PIPERAZINE AND 2-AMINO-2-METHYL-1-PROPANOL - MOHAMAD ZAHARI, NOR AFAF SYALSABILA (2019)
Researchers all around the world are looking for alternatives to conventional solvents for carbon dioxide absorption. One of the promising approaches is utilization of amino acid salts.